Pendampingan UMKM dalam Meningkatkan Kualitas Sumber Daya Manusia dan Pendapatan Keluarga - Maya Yusnita; Novita Herlissha; Reniati Reniati; Nanang Wahyudin; Padlun Fauzi; Khadijah Khadijah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Karya Makmur Village is one of the villages in the Pemali District Bangka Regency Bangka Belitung Islands Province. The problem of Karya Makmur Village that the knowledge of MSMEs actors is still quite low regarding MSME development strategies both in terms of Human Resources (HR), marketing and finance. In addition, MSMEs actors also do not have product licensing legality such as Halal Certification and Business Identification Number (NIB). The method of the program are outreach, education, training and mentoring. The stages of the activity consist of preparation, implementation, mentoring and evaluation. The implementation of the program has provided understanding, motivation, competency and skills in MSMEs development both in the fields of Human Resources (HR), Marketing, Finance and product licensing (Halal Certification and NIB). This activity will be periodically monitored and evaluated in order to maintain the sustainability of the program.